2017
DOI: 10.1161/hypertensionaha.117.09744
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B1 Receptor Promotes Neurogenic Hypertension Through Activation of Centrally Mediated Mechanisms

Abstract: Hypertension is associated with increased activity of the kallikrein-kinin system. Kinin B1 receptor (B1R) activation leads to vasoconstriction and inflammation. Despite evidence supporting a role for the B1R in blood pressure (BP) regulation, the mechanisms by which B1R could alter autonomic function and participate in the pathogenesis of hypertension remain unidentified. We sought to explore whether B1R-mediated inflammation contribute to hypertension and investigate the molecular mechanisms involved. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 44 publications
(58 reference statements)
0
40
0
Order By: Relevance
“…Evidence for a possible crosstalk between glutamate-induced excitotoxicity and impairment of ACE2 activity in primary cortical neurons has been reported in our previous study [ 8 ]. On the other hand, B1R blockade can reduce neuroinflammation, prevent autonomic dysfunction and sympathoexcitation, and attenuate hypertension in a mouse model of neurogenic hypertension [ 20 ]. However, the crosstalk between glutamate and B1R has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for a possible crosstalk between glutamate-induced excitotoxicity and impairment of ACE2 activity in primary cortical neurons has been reported in our previous study [ 8 ]. On the other hand, B1R blockade can reduce neuroinflammation, prevent autonomic dysfunction and sympathoexcitation, and attenuate hypertension in a mouse model of neurogenic hypertension [ 20 ]. However, the crosstalk between glutamate and B1R has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Western blots were performed on primary hypothalamic neuronal homogenates, as described previously [ 20 , 40 ]. Neuron samples were homogenized in 1X lysis buffer containing protease and phosphatase inhibitors cocktail (Roche) and incubated on ice for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies pharmacologically targeting the two receptors also revealed differential effects with B1R expression strongly responsive to inflammation (Sriramula and Lazartigues, 2017) and to changes in the environment (Ongali et al, 2003, Arganaraz et al, 2004. Furthermore, blockade of B1R in rats led to the improvement of cognitive function and agerelated cognitive decline (Prediger et al, 2008, Bitencourt et al, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…C57Bl6/J male mice (10–12 weeks old, n = 3/group) were anesthetized with isoflurane (2%) and implanted subcutaneously with a DOCA (1 mg/g body weight) pellet and switched to a 1% NaCl drinking solution, as described previously (Sriramula and Lazartigues 2017 ). After 3 weeks, mice were euthanized and the hypothalamus was dissected for protein extraction and Western blotting analysis, as mentioned above.…”
Section: Methodsmentioning
confidence: 99%